2020
DOI: 10.1371/journal.pone.0228737
|View full text |Cite
|
Sign up to set email alerts
|

The effect of liver enzymes on body composition: A Mendelian randomization study

Abstract: BackgroundHigher alanine transaminase (ALT), indicating poor liver function, is positively associated with diabetes but inversely associated with body mass index (BMI) in Mendelian randomization (MR) studies, suggesting liver function affects muscle mass. To clarify, we assessed the associations of liver enzymes with muscle and fat mass observationally with two-sample MR as a validation. MethodsIn the population-representative "Children of 1997" birth cohort (n = 3,455), we used multivariable linear regression… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
(70 reference statements)
0
2
0
Order By: Relevance
“…Alanine aminotransferase is an enzyme that is located primarily in the cytosol of hepatocytes, and thus, it is a specific marker for liver injury 10 . Many studies have confirmed the association between ALT and body composition 6,11 . However, some research has found no association between serum ALT and fat mass in women, 6 and the relationship between ALT and the body composition of postmenopausal women in China has not been reported, to date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alanine aminotransferase is an enzyme that is located primarily in the cytosol of hepatocytes, and thus, it is a specific marker for liver injury 10 . Many studies have confirmed the association between ALT and body composition 6,11 . However, some research has found no association between serum ALT and fat mass in women, 6 and the relationship between ALT and the body composition of postmenopausal women in China has not been reported, to date.…”
Section: Discussionmentioning
confidence: 99%
“…10 Many studies have confirmed the association between ALT and body composition. 6,11 However, some research has found no association between serum ALT and fat mass in women, 6 and the relationship between ALT and the body composition of postmenopausal women in China has not been reported, to date. The current study found that ALT was positively associated with the fat mass index in this sample.…”
Section: Re Sultsmentioning
confidence: 99%